Effectiveness of Learning Model Implementation STEM and Project Based Learning to Improve Students' Critical Thinking Skills - Budhyawan S. Bandjar; Mohammad Gamal Rindarjono; Singgih Prihadi (Eduvest - Journal of Universal Studies, 2024)
This research aims to describe the process and results of developing a STEM learning model using the PjBL model to improve students' critical thinking abilities. This type of research is a combination method of the Concurrent Triangulation model which consists of step one, qualitative research using the learning development model proposed by Kemp 1994, while step two is quantitative research using quasi experimental design research. The implementation of the development of this model was carried out at SMA Negeri 8 Ternate City, North Maluku Province involving 64 students in class students in experimental class 2 PjBL Model. Critical thinking ability data was taken using a test instrument with a reliability of 0.76. Data analysis was carried out using the one way unequal Anova test. The results of the research show that there is no significant difference in critical thinking skills between the STEM learning model and the PjBL model on critical thinking skills on the subject of Indonesian natural resource management in the large category.